Sensory quality of orange-fleshed sweetpotato cultivars as affected by curing and household-level storage methods - Atuna, R.A.; Amagloh, F.K.; Carey, E.E.; Low, Jan W. (Academic Journals, 2017)
A 2×2×3 factorial design was used to investigate the effect of two orange-fleshed sweetpotato cultivars, three curing treatments and two homestead storage methods on the general appearance, finger-feel firmness, sweetness and overall acceptability of boiled roots. The cultivars were Apomuden and Nane, and the two homestead storage methods were the sand box and the heap storage. In-ground curing (dehaulming) and field-piled curing, for seven days and then uncured treatment were the curing options investigated. A hedonic scale ranging from 1 = extremely dislike to 5 = like extremely was used. For cultivars, the sensory scores ranged from 3.20 to 3.84 (farming season I) and 3.32 to 3.93 (farming season II), indicating good consumer preference. Curing type significantly (p<0.05) influenced the sensory properties of roots in the second farming season. Storage type showed no significant difference (p > 0.05) in all sensory attributes in both farming seasons except for sweetness and the heap storage had significantly higher (3.84 vs. 3.47, p<0.0001; respectively) score relative to sand box in the first year. Apart from general appearance (3.64 vs. 3.32, p = 0.002) and finger-feel firmness (3.51 vs. 3.25; p = 0.006) in which females had a significantly higher score than males in the first farming season, all the other sensory attributes were similarly ranked by males and females for both years. In-ground and field-piled curing methods, there is increased consumer acceptability and it should be encouraged.